Guilt of Consumption Scale (ESCC): development and content validity of a psychological measure in Brazilian mothers. (Research, Society and Development, 2020)
This study aims to develop and evaluate the content of a measure about the maternal guilt in relation to consumption. The topic of consumer behavior is important in several areas of study and draws attention to new forms of affective compensation due to the demand for hours of work by the parents, influenced by exaggerated consumption attitudes that justify the low involvement with the children, which can generate a kind of guilt. In total, 120 mothers were evaluated, which were distributed in a sample with 20 of them acting as judge in the content evaluation, and the other sample, with 100 mothers, for analysis of discrimination and content representativeness of the items. All of them over 18, working and with children over the age of eight, responded to the Consumer Guilt Scale (mother version). Considering the statistical analyzes, it was observed that the scale of guilt showed quality and safety in the content expressed, as well as, discrimination and representativeness of the content. Thus, the measure of the guilt of consumption can be considered validated in its content, capable of measuring what was intended as a construct presented.